Pembelajaran IPA Berpendekatan Jelajah Alam Sekitar (JAS) Terhadap Hasil Belajar pada Kelas V SD - Putri, Dinda Anisyah; Hetilaniar, Hetilaniar; Dirgantara, Marvinda Rizki Dita (Indonesian Research Journal on Education, 2022)
The purposeof this study was to determine whether the approach to exploring the surrounding nature could improve science learning outcomes for fifth grade students at SD Negeri 32 Palembang. This research is a type of quantitative research using the experimental method of True-Experimental Design research in the form of Posttest-Only Design. The variables of this study consisted of the independent variable (X) namely the Surrounding Nature Exploration Approach (JAS) and the dependent variable (Y) namely learning outcomes. The population of this study were all fifth grade students of SD Negeri 32 Palembang, totaling 42 students who were selected using the Non-Probability Sampling technique with the Purposive Sampling method. Data collection techniques using tests and observations. The validity of the test instrument was tested using the product moment correlation formula and the reliability test using the split-half. The data analysis technique used the T test, which was carried out after the normality and homogeneity tests were known. The experimental class that was given treatment with the surrounding nature cruising approach (JAS) obtained an average posttest of 79,524 and the control class obtained an average posttest of 68,947. The results of the T-test with ttable 2.021 obtained tcount 2.521 it can be concluded that science learning approaches the Natural Exploration (JAS) approach to learning outcomes in class V SD.